HUBUNGAN TINGKAT STRESS DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI POSYANDU LANSIA PUSKESMAS TIGA DOLOK PANRIBUAN TAHUN 2022 - Tinah Tinah; Harijun kapabela Siregar (Poltekkes Kemenkes Medan, 2023)
One of the causes of increased blood pressure in hypertensive patients is stress. Stress is an unpleasant physical and psychological pressure, stress can stimulate the glands in the kidneys to release the hormone adrenaline and trigger the heart to beat faster and stronger, so that blood pressure increases. This study aims to determine the relationship between stress levels in the elderly and the incidence of hypertension in the elderly at the Elderly Health Center in Tiga Dolok Panribuan Health Center. This type of research is a type of quantitative research with descriptive correlation research methods. The sample in this study amounted to 42 respondents. The sampling technique used is total sampling. The research instruments were in the form of respondent demographic data, stress levels used the DASS (Depression Anxiety Stress Scale) questionnaire, and hypertension was measured using a sphygmomanometer, stethoscope and observation sheet. Data were analyzed using the sperman rho correlation test. The results of this study indicate that there is a relationship between stress levels and the incidence of hypertension in the elderly at Tiga Dolok Panribuan Health Center (p = 0.000). The conclusion obtained is that the better the elderly are in controlling their stress, the lower the risk of hypertension in the elderly. For future researchers, it is necessary to make efforts to prevent stress so that it can reduce the prevalence of hypertension in the elderly.